Social and Institutional Innovation in Self-Organising Cities - Giallorenzo, Flavia; Perrone, Camilla; Rossi, Maddalena (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
Today's scenario is characterized by a global connectivity space where uninterrupted streams of information, people, and goods flow, through multi-scale socio-economic processes. All of this requires rethinking well-accepted mental frames as individual capabilities, businesses actions, social and spatial agglomerations evolve in a new and unceasingly changing landscape. This book contributes to the debate on how cities are redefined in relation to the global connective space and the so-called knowledge-based economy. The authors explore the variable set of functional changes, which are intrinsically linked to the multiplicity of multi-scale processes. The book contains the proceedings of the conference "New sciences and actions for complex cities (Florence, Italy 14-15 December 2017)".